2018
DOI: 10.1016/j.jgr.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

High-performance liquid chromatography analysis of phytosterols in Panax ginseng root grown under different conditions

Abstract: BackgroundThe Panax ginseng plant is used as an herbal medicine. Phytosterols of P. ginseng have inhibitory effects on inflammation-related factors in HepG2 cells.MethodsPhytosterols (e.g., stigmasterol and β-sitosterol) in the roots of P. ginseng grown under various conditions were analyzed using high-performance liquid chromatography. The P. ginseng roots analyzed in this study were collected from three cultivation areas in Korea (i.e., Geumsan, Yeongju, and Jinan) and differed by cultivation year (i.e., 4 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…Sun reported the total saponin content in ginseng root hair as being higher than that in other parts of ginseng. Ginseng has drawn attention as a traditional medicine worldwide because of its various functions, such as anti‐diabetes, anti‐inflammatory, antioxidant and anticancer activities …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun reported the total saponin content in ginseng root hair as being higher than that in other parts of ginseng. Ginseng has drawn attention as a traditional medicine worldwide because of its various functions, such as anti‐diabetes, anti‐inflammatory, antioxidant and anticancer activities …”
Section: Introductionmentioning
confidence: 99%
“…Ginseng has drawn attention as a traditional medicine worldwide because of its various functions, such as anti-diabetes, anti-inflammatory, antioxidant and anticancer activities. [5][6][7][8][9][10][11][12][13] Baek et al 14 reported that heat processing led to chemical and structural changes, improving the biological activities. Extrusion has been considered as a high-temperature short-time process to produce commercial products for over 50 years, because of its high productivity, energy efficiency and versatility.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that ginseng cultivated in Jinan exhibited the highest ginsenoside Rc content (0.495 mg/g) and the highest total major ginsenoside content (0.931 mg/g). A recent study using ginseng samples cultivated in Geumsam, Yeongju, and Jinan showed that ginseng samples from Jinan also had the highest phytosterol content [16]. Phytosterol is another bioactive compound present in ginseng species.…”
Section: Resultsmentioning
confidence: 99%
“…BSS was determined by the HPLC method previously developed by Lee et al . 28 . An HPLC system (Shimadzu, Tokyo, Japan) was used.…”
Section: Methodsmentioning
confidence: 99%